Ответ:
x ∈ [ - 5 ; 2 ].
Объяснение:
11 - ( x + 1 )² ≥ x ;
11 - ( x² + 2x + 1 ) ≥ x ;
11 - x² - 2x - 1 ≥ x ;
10 - x² - 2x ≥ x ;
- x² - 2x + 10 ≥ x ;
- x² - 2x + 10 - x ≥ 0 ;
- x² - 3x + 10 ≥ 0 ;
- x² - 3x + 10 = 0 ;
a = - 1 ; b = - 3 ; c = 10 ;
D = b² - 4 * a * c = ( - 3 )² - 4 * ( - 1 ) * 10 = 9 + 40 = 49 ;
x₁,₂ = ( - b ± √D )/(2*a) ;
x₁ = (-(-3-√49))/(2*(-1)) = (3-7)/(-2) = (-4)/(-2) = 4/2 = 2 ;
x² = (-(-3+√49)/(2*(-1))= (3+7)/(-2) = 10/(-2) = - 5 ;
Методом интервалов : фото.
⇒ ⇒ x ∈ [ - 5 ; 2 ].
________________________________________
( a + b )² = a² + 2ab + b².
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
x ∈ [ - 5 ; 2 ].
Объяснение:
11 - ( x + 1 )² ≥ x ;
11 - ( x² + 2x + 1 ) ≥ x ;
11 - x² - 2x - 1 ≥ x ;
10 - x² - 2x ≥ x ;
- x² - 2x + 10 ≥ x ;
- x² - 2x + 10 - x ≥ 0 ;
- x² - 3x + 10 ≥ 0 ;
- x² - 3x + 10 = 0 ;
a = - 1 ; b = - 3 ; c = 10 ;
D = b² - 4 * a * c = ( - 3 )² - 4 * ( - 1 ) * 10 = 9 + 40 = 49 ;
x₁,₂ = ( - b ± √D )/(2*a) ;
x₁ = (-(-3-√49))/(2*(-1)) = (3-7)/(-2) = (-4)/(-2) = 4/2 = 2 ;
x² = (-(-3+√49)/(2*(-1))= (3+7)/(-2) = 10/(-2) = - 5 ;
Методом интервалов : фото.
⇒
⇒ x ∈ [ - 5 ; 2 ].
________________________________________
( a + b )² = a² + 2ab + b².